Caries risk assessment in young adults using Public Dental Service guidelines and the Cariogram—a comparative study. (May 2013) - Hänsel Petersson, Gunnel; Ericson, Ewa; Isberg, Per-Erik; Twetman, Svante
Abstract Objectives. To investigate the caries risk profiles in young adults and to compare the risk classification using the Public Dental Service (PDS) guidelines with a risk assessment program, the Cariogram. Materials and methods. All 19-year-old patients registered at eight public dental clinics were invited to participate (n = 1699). The study group who completed the baseline examination consisted of 1295 subjects representing 10% of all 19 year-olds attending dental care at the PDS in Skåne, Sweden. A risk classification of each patient was made by the patient's regular team according to the PDS guidelines. A research team collected whole saliva samples and information from a questionnaire and a structured interview in order to calculate risk according to the Cariogram model. Results. The mean DFS value was 4.9 and 23% of the patients were registered as caries-free (DFS = 0). The PDS risk classification was predominantly based on past caries and/or present caries activity. The majority was classified as 'some risk', while 16.7% were assessed as being of 'high' or 'very high risk'. The corresponding value for the two highest risk groups in the Cariogram model was 17.4%. The agreement between the two models was found acceptable (77.5%) for those assessed as low risk, while discrepancies were disclosed among those classified with higher risks. Conclusions. Although the proportion of subjects assessed with high or very high risk was similar using the PDS guidelines and the Cariogram model, the agreement between the models was fair. An acceptable agreement was only disclosed for the low risk category.